PEREMPUAN PENDIDIK GENERASI ISLAM YANG TANGGUH - Asmaunizar Asmaunizar (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2021)
Mother as a noble woman figure described by Islam plays an important role in every cycle of time. Both parents are the most meritorious human beings, especially mothers are like lamps in lighting the lantern of life. Their sacrifices and services are so great, their time, energy, thought, attention and funds they give and sacrifice without limit. Especially mothers when they are pregnant, giving birth risking their lives, not a few of them die at the time of giving birth to the baby they want. Mother's sacrifice continues from time to time as the child develops in forming and creating a Rabbani generation that is in accordance with Islamic guidance, this cannot be separated from the mother's education itself. Children should honor their parents, especially mothers with noble character.